A lectin receptor-like kinase controls self-pollen recognition in Phlox - Grace A. Burgin; Nia Faith Lewis; Robin Hopkins (Proceedings of the National Academy of Sciences, 2026)
Self-incompatibility (SI) describes a widespread collection of genetic mechanisms in flowering plants used to specifically recognize and reject self-pollen. These mechanisms are fundamental to plant sexual reproduction and offer valuable insight into the molecular basis of cell–cell communication and self-recognition more broadly. Here, we leverage an independent evolution of SI in the lineage containing Phlox (Polemoniaceae) to identify the gene causing self-pollen recognition which we name Phlox drummondii Pistil Identity Receptor Kinase (PdPIRK) . Recognition of self-pollen associates with a single genomic region containing the Phlox S -locus. We generate predictions regarding how S -loci must function and evolve to identify a single candidate gene within this S -associated region. This gene, PdPIRK , is highly and specifically expressed in the pistil and has exceptionally high polymorphism maintained by negative frequency-dependent selection, two hallmarks of self-pollen recognition genes. Functional validation with gene silencing confirms that PdPIRK is necessary for self-incompatibility, and we further demonstrate allele-specific activity, confirming its role in self-pollen recognition per se. PdPIRK encodes a G-type lectin receptor-like kinase, which is a member of the same gene family as SRK , the gene controlling self-pollen recognition in the distantly related Brassicaceae. Our findings suggest the presence of genetic constraints or paths of least resistance governing how S -loci evolve and add to our understanding of the diverse molecular mechanisms through which organisms achieve self-recognition.